Peran Islamic Social Finance di Indonesia Menuju Sustainable Development Goals (SDGs) - Yenni Samri Juliati Nasution; Saparuddin Siregar; Zen, M. Afif Shahputra; Edi Faisal Harahap; Rodi Syafrizal; Dewi Sundari (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This article discusses the important role of Islamic Social Finance (ISF) in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia. ISF, which includes instruments such as zakat, infaq, sadaqah, and waqf, has great potential to contribute significantly to poverty alleviation, education improvement, public health, and environmental sustainability. Through effective management and collaboration between stakeholders, ISF can improve the social and economic welfare of the community, especially among vulnerable groups. However, challenges in optimizing ISF instruments are considerable, including the lack of understanding of the government and stakeholders in implementing ISF and the recent development of digital platforms. This article discusses the importance of ISF in achieving the SDGs and recommends the development of digital platforms, integrated Islamic social financing models, and community-based education initiatives to increase the effectiveness of ISF. With an innovative and collaborative approach, ISF is expected to be an effective tool in enhancing the role of Islamic economics in Indonesian society to achieve the SDGs and create a sustainable positive impact on society and the environment in Indonesia. For this reason, a development driving force is needed so that the SDGs and ISF targets can be achieved. This research is limited by inadequate digital infrastructure, unclear regulations, and a lack of trained human resources. Future research should focus on raising public awareness of ISF, developing supportive regulations, strengthening collaboration between the government and financial institutions, and exploring innovations in ISF products.